Evaluation of Hallobumil Using the System Usability Scale and User Experience Methods Among Pregnant Women in Semarang - Zahra, Alvieatuz; Wulandari, Respati (Health Science UDINUS, 2025)
Hallobumil is a mobile health application designed to provide information and education for pregnant women. Usability and user experience are critical to ensuring ease of use, relevance, and engagement, ultimately supporting better pregnancy outcomes. This study aimed to evaluate the usability and user experience of the Halo Bumil application among pregnant women in Semarang, Indonesia. A descriptive cross-sectional study was conducted involving 390 pregnant women from 15 community health centers. Data were collected through direct interviews using structured questionnaires based on the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) and analyzed descriptively. The mean age of participants was 28.5 ± 5.5 years; most had senior high school education (57.4%), earned less than the local minimum wage (63.6%), were housewives (58.5%), and received health information from healthcare providers (74.1%). The mean SUS score was 62 (marginal), corresponding to Grade D, with an adjective rating of “OK.” The mean UEQ scores were positive across all dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Overall, the Halo Bumil application is considered suitable as a digital information medium to support pregnancy. These findings provide valuable insights for developers to enhance features and user-friendliness.